Citizenship education courses are used as a means of implementing multicultural education at the Politeknik Pelayaran Sorong - Permady, Gigieh Cahya; Zulfikar, Gilang; Siswanto, Siswanto; Nanggala, Agil (Journal of Research in Instructional, 2023)
The importance of intercultural education in vocational education motivates this study. This study aims to give a "rationalization" of the relevance of optimizing education, particularly civic education courses, as a kind of intercultural learning. This study employs a qualitative approach combined with descriptive methodologies. Study topic requirements do this and acquire in-depth information that incorporates social reality, and the findings will be conveyed subsequently in the form of reports and narrative descriptions. The study's findings show that the application of multicultural education in citizenship education courses at the Sorong Shipping Polytechnic can be seen in three major parts of the learning process: planning as seen from the lesson plan created independently by the lecturer, implementation of the material presented, and methods. Evaluation criteria for assessing learning outcomes that incorporate the weight of attitude assessment throughout the learning process are utilized. The cadets' concept of multiculturalism may be demonstrated via three multicultural components: their understanding of diversity awareness, openness to differences, and fair and equitable treatment.